Relationship of Social Capital and Collective Action in The Development of Tourism Village - Allifia Rizqi Suryandhani; Gunawan Prayitno; Surjono Surjono (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The development of a tourist village focuses on the active involvement of the local community and is inseparable from the ties of social capital they have. Social capital is a picture of social life in which participants carry out joint actions effectively to achieve common goals. However, Gunungsari Village has yet to realize its social capital by utilizing collective effort to build and develop village potential, so the whole community cannot enjoy the development of Gunungsari Village into a tourism village. This study aims to identify what indicators form social capital variables and the relationship between social capital variables and collective action in developing tourism villages. This quantitative study uses structural equation model analysis to determine the relationship between variables. Based on the findings, it is known that social networks in forming social capital are 0.445. Furthermore, social capital comprises a community action of 0.950. Therefore, networking in social capital at all levels of society is one of the primary keys to the smooth implementation of development.